Assessment and rehabilitation of neglect using virtual reality: a systematic review - Pedroli, Elisa; Serino, Silvia; Cipresso, Pietro; Pallavicini, Federica; Riva, Giuseppe (Frontiers in Behavioral Neuroscience, 2015)
After experiencing a stroke in the right hemisphere, almost 50% of patients showed Unilateral Spatial Neglect (USN). In recent decades, Virtual Reality (VR) has been used as an effective tool both for the assessment and rehabilitation of USN. Indeed, this advanced technology allows post-stroke patients to interact with ecological and engaging environments similar to real ones, but in a safe and controlled way. To provide an overview of the most recent VR applications for the assessment and rehabilitation of USN, a systematic review has been carried out. Since 2010, thirteen studies have proposed and tested innovative VR tools for USN. After a wide description of the selected studies, we discuss the main features of these VR tools in order to provide crucial indications for future studies, neurorehabilitation interventions and clinical practice.